Changes in indicators of the prooxidant-antioxidant system in patients with drug addiction during the rehabilitation - I. M. Bykov; D. A. Lubchenko; К. A. Popov; Ya. E. Denisova; A. N. Stolyarova; M. A. Popova (Инновационная медицина Кубани)
Background: Despite the positive dynamics in this scientific area, the prevalence of drug pathology in Russia and other countries of the world remains unfavorable. Determination of laboratory markers of pathobiochemical processes which are characteristic to the patients with substance use disorder is promising from the standpoint of monitoring the course of the disease and evaluating the effectiveness of therapy.Objective: To determine the characteristic changes in oxidative homeostasis of patients with addiction to psychostimulants and opioids at the rehabilitation and anti‑relapse stage.Material and methods: The study was performed with the participation of 20 relatively healthy male volunteers and 18 male patients with addiction to opioids or psychostimulants who then became participants of the rehabilitation and anti‑relapse course of treatment. Changes in oxidative stress markers during rehabilitation and anti‑relapse treatment were studied.Results: In comparison to the control values at the initial stage of the study, patients of the main group demonstrated decreased values of the iron‑reducing ability of blood plasma – by 25%, as well as those of the sorption radical ability of blood plasma – by 30%; the content of thiol groups of blood plasma proteins decreased by 24% while the concentration of glutathione in erythrocyte suspension lowered by 26%. The level of TBA‑reactive products in erythrocyte suspension corresponded to the control level. The performed rehabilitation manipulations contributed to the partial normalization of oxidative homeostasis, which was confirmed by a statistically significant increase in the ability of radical sorption of blood plasma by 20% and the concentration of reduced glutathione in erythrocyte suspension by 28% in comparison to the initial values of the corresponding parameters in patients of the 2nd group. The TBA‑reactive products remained within the control values.Conclusion: The studied markers are suitable for monitoring the state of oxidative homeostasis in patients with opioid or psychostimulant addiction, the imbalance of which at the end of the rehabilitation and anti‑relapse stage also indicates the prospects for strengthening the antioxidant component as part of drug or nutritional correction.